Contribution of Non-agricultural Sector in Economic Development of Nepal (Patan Pragya, 2022)
The non-agricultural sector has made a significant contribution to the Nepalese economy. The non-agriculture sector now contributes 76.1 percent of GDP. In the fiscal year 2078/2079, the per capita income rises by 10.8 percent as a result of this contribution. In the fiscal year 2078/2079, itis anticipated that this income would rise to US$ 1381. The per capita income for the fiscal year2077/2078 was only US$1246. GDP growth rates from the industrial and service sectors are 5.05percent and 4.43 percent, respectively, in the non-agriculture sector. Average percentage of total GDP for the previous five years: 65.7 percent, 65.9 percent, 68.6 percent, and 74.9 percent for 2059/60 to 2063/64, 2064/65 to 2068/69, 2069/70 to 2073/74, and 2074/75 to 2078/79respectively.The average growth rate for this industry over the thirteenth plan period is 3.4percent. Likewise, 37.2 percent of revenue in 2010/11 came from industries outside than agriculture. In Nepal, 21.6 percent of the population continues to live in poverty. Thus, it is intended to reduce poverty from 21.6 percent to 18 percent by the end of the 14th plan period and to eradicate it entirely by 2030. As a result, the non-agricultural sector will assist Nepal in moving from a less developed to a middle-income country. Hence, this study focuses on the contribution of non-agriculture sector in economic development of Nepal.